Paradigm Shift from Waste to Wealth through Biomass Conversion Technologies: A Panacea for Energy, Health and Environmental Challenges in Nigeria (London Journal of Engineering Research, 2022)
The over-dependence on fossil fuel, estimated to be exhausted in less than five decades is not sustainable and economical to the most populous country in Africa. Currently, the country is battling with insufficient energy, polluted environment and health challenges due to inequality in energy generation and consumption which promote the use of generators in the country. Meanwhile, exploitation of biomass to energy has been successfully adopted by advanced countries to break the fossil fuel monopoly and curtail its adverse effects on environment and health. This paper projected biomass conversion technology as a panacea to the energy, environmental and health challenges. Of the conversion technologies reviewed, biodigestion has huge potential in biogas production. The technology is cheap and the feedstock is readily available for exploitation at communal or individual level making it an attractive alternative to attain energy self-sufficiency. Presently, there are several collaborative efforts between Nigeria and several countries with respect to biogas generation. It was found that about 20 biogas pilot plant has been operational within the country. However, replication of the technology in different part of the country is challenged by lack of technical know-how, inadequate fund and lack of awareness. It is hoped that more can be achieved as the low level development of the technology is not encouraging. With government interventions and support from non-governmental organizations and other individual in the country, biogas plant can be constructed in all communities to replace generators thereby eliminating the energy, environmental and health challenges.
Keywords: biomass; Conversion Technology; biodigestion; biogas; Biodigestion and Biogas